BCL-3 and Î²-catenin signaling and tumor staging in colorectal cancer - Zhang, Shanhong; Yin, Changqing (Cellular and Molecular Biology, 2020)
Colorectal cancer (CBC) is the third most common cancer in men and the second most common cancer in women in the world, as well as the second leading cause of death among the world's cancers. In this study, to identify the genes involved in the CRC clinical outcomes, the expression of B cell leukemia/lymphoma 3 (BCL-3) gene in patients with colorectal cancer was investigated along with serum level of Î²-catenin. In this study, samples of 23 patients with colorectal cancer were prepared. mRNA was extracted and then cDNA was prepared for evaluation of PCR. Then, with specific primers for the BCL3, a semi-quantitative RT-PCR test was performed. The enzyme-linked immunosorbent assay (ELISA) was used to assess the serum level of Î²-catenin. In this study, 23 men with an average age of years were included. BCL-3 expression in tumor tissue was significantly higher than its level in healthy tissue (P=0.021). BCL-3 expression at stage 0 of the tumor was significantly lower than at all other stages (P<0.05), and the comparison between the rest of the CRC stages was not significant (P>0.05). The median of serum Î²-catenin levels in the patients was 32.83 (22.45, 46.09). There was no significant difference in the amount of serum Î²-catenin between all 5 stages of the disease and in terms of lymph node metastasis. There were no relationships between age, BMI, smoking history, familial CRC history, and BCL-3 or Î²-catenin serum levels (P>0.05). In this study, the expression of the BCL-3 gene in tumor specimens was high. It can be said that the BCL-3 gene can act as one of the genes involved in colorectal cancer, along with some genes such as Î²-catenin. While BCL-3 was associated with a higher stage of CRC, Î²-catenin didn't show such a relationship with CRC.